Modified negative electrode material as well as preparation method and application thereof

By using the surface cladding of the aggregate structure formed by self-stacking of nanosilicon, pore-forming agent and electrolyte in the lithium-ion battery negative electrode material, the structural powdering and side reaction problems caused by volume expansion of the silicon-based negative electrode material are solved, and the conductivity and cycling performance are improved.

CN119920868APending Publication Date: 2025-05-02GREE ALTAIRNANO NEW ENERGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411834538.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

During the charging and discharging process, the silicon-based negative electrode material has structural powdering, many side reactions with the electrolyte, serious capacity attenuation, and poor conductivity.

Method used

A modified negative electrode material is used, including an inner layer and an outer layer, the inner layer is composed of graphite, and the outer layer contains an aggregate structure formed by self-stacking of nanosilicon, pore-forming agent and electrolyte, and the lithium carbon mixture is filled in the gaps of the aggregate structure and extends to the outer surface to form a surface cladding layer.

Benefits of technology

It effectively weakens the volume expansion of silicon, reduces the risk of structural powdering and side reactions, improves the conductivity, stability and cycling performance of the negative electrode material, and enables the specific capacity to be fully utilized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920868A_ABST
    Figure CN119920868A_ABST
Patent Text Reader

Abstract

The invention provides a modified negative electrode material as well as a preparation method and application thereof. The modified negative electrode material comprises an inner layer and an outer layer coating the surface of the inner layer, the inner layer comprises graphite, the outer layer comprises an aggregation structure body and a lithium-carbon mixture, the aggregation structure body is formed by self-accumulation of nanometer silicon, a pore-forming agent and an electrolyte, gaps are formed in the aggregation structure body, the gaps of the aggregation structure body are filled with the lithium-carbon mixture, and the lithium-carbon mixture is formed by self-accumulation of nanometer silicon, a pore-forming agent and an electrolyte. And the coating layer extends to the surface of the outer layer to form a surface coating layer. In the modified negative electrode material, the nanometer silicon and the pore-forming agent cooperate with each other, volume expansion of silicon in the charging and discharging process is effectively weakened, diffusion and migration of lithium ions in the negative electrode material are promoted by adding the electrolyte, and the lithium-carbon mixture in the outer layer not only improves the conductivity of the negative electrode material, but also improves the surface stability of the negative electrode material. All the components cooperate with one another, so that the conductivity, stability and cycle performance of the negative electrode material are effectively improved, and the specific capacity is fully exerted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a modified negative electrode material, a preparation method thereof and an application thereof. Background Art

[0002] With the rapid development of technology products such as electric vehicles and smart phones, the energy density of lithium-ion batteries is increasingly required. Currently, the energy density of lithium-ion batteries on the market is mostly lower than 300Wh / kg, and they mainly use a combination of high-nickel positive electrode materials and graphite negative electrode materials. In order to further improve the energy density of batteries, it is necessary to continue to increase the specific capacity of positive or negative electrode materials.

[0003] At room temperature, the lithium-rich product Li formed by the silicon in the silicon-based negative electrode material and lithium 3.75 The theoretical specific capacity of Si phase is as high as 3572mAh / g, far exceeding the theoretical specific capacity of graphite negative electrode 372mAh / g. Silicon-based materials are currently in the stage of small-scale commercial application. When used with high-nickel positive electrode materials, the energy density of lithium-ion batteries can reach 300-400Wh / kg. It is considered to be a strong competitor for the next generation of lithium-ion battery negative electrode materials. However, during the repeated charge and discharge process of silicon-based negative electrode materials, Si and Li 3.75 The Si phase transition will produce a huge volume expansion (up to 270%), which may lead to structural pulverization of the electrode material, increased side reactions between the surface and the electrolyte, and ultimately a rapid decrease in battery capacity. In addition, silicon has relatively poor electrical conductivity.

[0004] The patent with application number 202010119379.3 discloses an improved silicon-carbon composite negative electrode material for lithium-ion batteries and its preparation method. This method improves the electronic conductivity of silicon-carbon materials and increases the combined specific surface area of ​​lithium ions and silicon by the flaky structure of nano-silicon, multi-layer carbon coating and tiny pores generated inside the carbon layer. The tiny pores in the internal carbon layer can improve the rate capability of silicon-carbon materials. However, a large number of tiny pores may increase side reactions with the electrolyte and affect the specific capacity of the material, especially during continuous charging and discharging.

[0005] Therefore, it is necessary to continue to optimize material structure and surface treatment to improve the performance of silicon-based negative electrode materials and provide more efficient and lasting energy solutions for electric vehicles and mobile devices. Summary of the invention

[0006] The main purpose of the present invention is to provide a modified negative electrode material, a preparation method and application thereof, so as to solve the problems of structural pulverization, many side reactions between the surface and the electrolyte, severe capacity attenuation and poor conductivity caused by large volume expansion changes of silicon-based negative electrode materials in the prior art.

[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a modified negative electrode material is provided, comprising an inner layer and an outer layer coated on the surface of the inner layer, wherein the inner layer comprises graphite; the outer layer comprises an aggregate structure and a lithium-carbon mixture; the aggregate structure is formed by self-stacked nano-silicon, a pore-forming agent and an electrolyte, and has gaps in the aggregate structure; the lithium-carbon mixture is filled in the gaps of the aggregate structure and extends to the surface of the outer layer to form a surface coating layer.

[0008] Furthermore, in the modified negative electrode material, the thickness ratio of the inner layer to the outer layer is (0.25-16):1; preferably, the thickness of the outer layer is 200-1000 nm, wherein the thickness of the surface coating layer is 5-100 nm; and / or, the weight ratio of nano-silicon to graphite is (10-80):(10-80); and / or, the weight ratio of the pore former to graphite is (1-10):(10-80); and / or, the weight ratio of the electrolyte to graphite is (2-30):(10-80); and / or, the weight ratio of the lithium-carbon mixture to graphite is (4-40):(10-80).

[0009] Furthermore, in the modified negative electrode material, the particle size D50 of graphite is 5 to 30 μm; and / or the particle size D50 of nano-silicon is 10 to 150 nm; and / or the diameter of the pore-forming agent is 5 to 200 nm.

[0010] Further, the pore-forming agent includes one or more of silver nanowires, copper nanowires, carbon nanotubes, carbon fibers, zinc oxide nanorods, silicon carbide nanowires, boron nitride nanowires and graphene; and / or, the electrolyte includes lithium aluminum oxide, lithium phosphate, lithium tantalate, lithium zirconate, LiF, lithium rubidium oxide, Li7La3Zr2O 12 , Li 3x La (2 / 3)-x M (1 / 3)-2x TiO3、Li 1+y Al y Ti 2-y (PO4)3 and Li 16-2z N z (TO4)4; wherein M represents a vacancy, N includes one or more of Zn, Cu, V and Ti, T includes Ge and / or P, 0.05≤x≤0.15, 0≤y≤0.5, 1≤z≤7; and / or, the lithium-carbon mixture includes a lithium-containing substance, and the lithium-containing substance includes one or more of LiCl, Li2C2O4, LiNO3, Li2CO3, CH3COOLi, LiOH·H2O, LiF, LiPF6, LiFSI, LiBF4, LiBOB and LiTFSI.

[0011] According to another aspect of the present invention, a method for preparing the above-mentioned modified negative electrode material is provided, wherein the raw materials of the modified negative electrode material include graphite, a silicon source, a pore-forming agent, an electrolyte, a carbon source, a lithium source and a dispersant; the dispersant is divided into two parts, namely a first dispersant and a second dispersant; the preparation method comprises the following steps: step S1, firstly mixing the first dispersant, the silicon source, the electrolyte, the graphite and the pore-forming agent for a first time to obtain a first slurry; the silicon source D50 particle size in the first slurry is less than 1000nm; step S2, spray-drying the first slurry for a first time to obtain a first solid; step S3, mixing the first solid with the carbon source, the lithium source and the second dispersant for a second time to obtain a second slurry; step S4, spray-drying the second slurry for a second time and calcining in a non-reactive atmosphere in sequence to obtain the modified negative electrode material.

[0012] Further, the graphite includes one or more of natural graphite, flake graphite, artificial graphite and mesophase carbon microspheres; and / or, the silicon source includes one or more of silicon powder, ferrosilicon alloy, silicon-magnesium alloy, silicon-calcium alloy and silicon-manganese alloy; preferably, the D50 particle size of the silicon source is 1 to 10 μm; and / or, the carbon source includes polyethylene, polypropylene, polystyrene, phenolic resin, urea-formaldehyde resin, melamine formaldehyde resin, epoxy resin, asphalt, unsaturated polyester resin, polyurethane, citric acid, malic acid, glucose, sorbic acid, sucrose, polyacrylic acid, polyvinyl pyrrolidone, ascorbic acid, asphalt, tartaric acid and carboxymethyl One or more of cellulose; and / or, the lithium source includes one or more of LiCl, Li2C2O4, LiNO3, Li2CO3, CH3COOLi, LiOH·H2O, LiF, LiPF6, LiFSI, LiBF4, LiBOB and LiTFSI; and / or, the first dispersant and the second dispersant are independently selected from one or more of ethanol, acetone, N-methylpyrrolidone, N,N-dimethylformamide, isopropanol, ethyl acetate, propylene carbonate, butyrolactone, dimethyl sulfoxide, water, toluene, xylene, tetrahydrofuran and acetonitrile.

[0013] Further, in step S1, the first dispersant is divided into two parts, namely a first sub-dispersant and a second sub-dispersant, and the first mixing includes the following steps: step S11, stirring and ball-milling the first sub-dispersant, a silicon source, and an electrolyte to obtain a first sub-slurry; step S12, adding the second sub-dispersant, graphite and a pore-forming agent to the first sub-slurry, performing a first grinding, and obtaining a first slurry; preferably, the stirring speed is 10 to 60 Hz, and the time is 1 to 10 h; and / or, the ball milling speed is 800 to 2500 r / min, and the time is 8 to 48 h; and / or, the first grinding speed is 2000 to 5000 r / min, and the time is 1 to 8 h; and / or, in terms of weight percentage, the solid content in the first slurry is 8 to 25%.

[0014] Further, in step S3, the second mixing is a second grinding, the rotation speed is 2000-5000r / min, and the time is 1-8h; and / or, in terms of weight percentage, the solid content in the second slurry is 7-20%; and / or, independently, the inlet temperature of the first spray drying and the second spray drying is 200-800°C, and the outlet temperature is 80-200°C; and / or, in step S4, the calcination temperature is 500-1000°C, the time is 2-10h, and the non-reactive atmosphere includes inert gas and / or nitrogen, and the inert gas includes argon and / or neon.

[0015] According to another aspect of the present invention, a modified negative electrode is provided, comprising the modified negative electrode material.

[0016] According to another aspect of the present invention, a battery is provided, comprising the modified negative electrode, a positive electrode and an electrolyte.

[0017] In the modified negative electrode material of the present invention, nano silicon and pore formers cooperate with each other, effectively weakening the volume expansion of silicon during the charge and discharge process, and reducing the risk of cracking and pulverization of silicon-based materials due to their own stress. The addition of electrolyte promotes the diffusion and migration of lithium ions in the negative electrode material, so that the capacity of the negative electrode material is fully utilized. The lithium-carbon mixture in the outer layer not only improves the conductivity of the negative electrode material, but also reduces the side reactions between the electrolyte and the negative electrode material, thereby improving the surface stability of the negative electrode material, so that the specific capacity of the negative electrode material is fully utilized. In the modified negative electrode material of the present invention, the various components cooperate with each other, effectively improving the conductivity, stability and cycle performance of the negative electrode material, and the specific capacity is fully utilized. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 A schematic diagram of the preparation process of the modified negative electrode material of Example 1 of the present invention is shown;

[0020] Figure 2 The schematic diagram of the structure of the modified negative electrode material of Example 1 of the present invention is shown;

[0021] Figure 3 The SEM morphology of the modified negative electrode material of Example 1 of the present invention is shown;

[0022] Figure 4 A cross-sectional view of a modified negative electrode material according to Example 1 of the present invention is shown; and

[0023] Figure 5The EDS graph of the modified negative electrode material of Example 1 of the present invention is shown.

[0024] in, Figure 2 The following reference numerals are included:

[0025] 1. Graphite; 2. Nano-silicon; 3. Electrolyte; 4. Pore-forming agent; 5. Lithium-carbon mixture filling the gaps in the aggregated structure; 6. Surface coating formed by the lithium-carbon mixture extending to the outer surface. DETAILED DESCRIPTION

[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0027] As described in the background of the present invention, the prior art has the problems of structural pulverization, many side reactions between the surface and the electrolyte, severe capacity attenuation, and poor conductivity caused by large volume expansion changes of silicon-based negative electrode materials. In order to solve the above problems, in a typical embodiment of the present invention, a modified negative electrode material is provided, including an inner layer and an outer layer coated on the surface of the inner layer, the inner layer includes graphite; the outer layer includes an aggregate structure and a lithium-carbon mixture; the aggregate structure is formed by self-accumulation of nano-silicon, a pore-forming agent and an electrolyte, and the aggregate structure has gaps; the lithium-carbon mixture is filled in the gaps of the aggregate structure and extends to the surface of the outer layer to form a surface coating layer.

[0028] The modified negative electrode material of the present application includes a graphite inner layer and an outer layer coated on the graphite surface. The surface of the outer layer of the modified negative electrode material of the present application is only a surface coating layer formed by a lithium-carbon mixture, which can not only improve the conductivity of the negative electrode material, but also reduce the side reaction between the electrolyte and the negative electrode material, thereby helping to improve the surface stability of the negative electrode material and give full play to the specific capacity of the negative electrode material.

[0029] The region between the graphite core and the outer surface also includes a lithium-carbon mixture, and the lithium-carbon mixture exists in the gap of the aggregate structure formed by the self-accumulation of nano-silicon, pore-forming agent and electrolyte, and the lithium-carbon mixture can also improve the conductivity of the negative electrode material. In addition, the aggregate structure in this region also contains nano-scale silicon and pore-forming agent. Nano-silicon has the characteristics of small size and large specific surface area, which can prevent the occurrence of crushing caused by volume expansion and reduce the degree of volume expansion. The pore-forming agent can form a pore structure in this region, increase the contact area between lithium ions and silicon and graphite, and can also provide a buffer space for the volume expansion of silicon. Nano-silicon and pore-forming agent cooperate with each other, which can effectively weaken the volume expansion of silicon during the charge and discharge process, reduce the risk of rupture and pulverization of silicon-based materials due to their own stress, and thus help to improve the cycle stability of negative electrode materials. Moreover, nano-silicon has high theoretical capacity, high electronic conductivity, and good ion diffusivity, which can significantly improve the energy density, charge and discharge rate and cycle life of negative electrode materials.

[0030] Secondly, the aggregate structure of the present application also includes an electrolyte. The electrolyte and nano-silicon are mixed with each other and distributed around the graphite, which can promote the diffusion and migration of lithium ions in the negative electrode material and fully utilize the capacity of the negative electrode material.

[0031] In summary, in the modified negative electrode material of the present application, silicon is nano-sized and pore-forming is designed, and the nano-silicon and pore-forming agent cooperate with each other, which can effectively weaken the volume expansion of silicon during the charging and discharging process, and reduce the risk of cracking and pulverization of silicon-based materials due to their own stress. The addition of electrolyte can promote the diffusion and migration of lithium ions in the negative electrode material, so that the capacity of the negative electrode material can be fully utilized. The lithium-carbon mixture in the outer surface coating layer can not only improve the conductivity of the negative electrode material, but also reduce the side reactions between the electrolyte and the negative electrode material, which is beneficial to improve the surface stability of the negative electrode material and give full play to the specific capacity of the negative electrode material. In the modified negative electrode material of the present application, the various components cooperate with each other, which can effectively improve the conductivity, stability and cycle performance of the negative electrode material, and the specific capacity can be fully utilized.

[0032] In a preferred embodiment, the thickness ratio of the inner layer to the outer layer is (0.25-16):1; and / or, preferably, the thickness of the outer layer is 200-1000 nm, wherein the thickness of the surface coating layer is 5-100 nm. Under the above conditions, not only can the side reaction between the negative electrode material and the electrolyte be more effectively suppressed, but also the electronic conductivity of the negative electrode material can be further improved, so that the specific capacity of the negative electrode material can be more fully utilized.

[0033] After a large number of experimental studies, the inventors continuously adjusted and improved the composition ratio of the negative electrode material to optimize the material structure and surface treatment to further improve the energy density, cycle life and conductivity of the material. In a preferred embodiment, in the modified negative electrode material, the weight ratio of nano-silicon to graphite is (10-80): (10-80); and / or, the weight ratio of the pore former to graphite is (1-10): (10-80); and / or, the weight ratio of the electrolyte to graphite is (2-30): (10-80); and / or, the weight ratio of the lithium-carbon mixture to graphite is (4-40): (10-80). Under the above conditions, the comprehensive performance of the negative electrode material is better, and the structural pulverization of the silicon-based negative electrode material caused by the large volume expansion change can be more effectively suppressed, the side reaction between the negative electrode material and the electrolyte is reduced, and the conductivity of the negative electrode material is improved.

[0034] In a preferred embodiment, the particle size D50 of graphite is 5 to 30 μm; and / or the particle size D50 of nano-silicon is 10 to 150 nm; and / or the diameter of the pore-forming agent is 5 to 200 nm. Under the above conditions, graphite, nano-silicon and pore-forming agent can achieve more comprehensive synergy, the conductivity of the negative electrode material is higher, the diffusion rate of lithium ions is faster, the charge and discharge rate is faster, and the volume change of silicon during the charge and discharge process is smaller, the mechanical stability is higher, and the cycle stability and safety are higher.

[0035] The pore-forming agent, electrolyte and lithium-containing material can be selected from conventional types in the battery field. In a preferred embodiment, the pore-forming agent includes one or more of silver nanowires, copper nanowires, carbon nanotubes, carbon fibers, zinc oxide nanorods, silicon carbide nanowires, boron nitride nanowires and graphene; and / or the electrolyte includes lithium aluminum oxide, lithium phosphate, lithium tantalate, lithium zirconate, LiF, lithium rubidium oxide, Li7La3Zr2O 12 , Li 3x La (2 / 3)-x M (1 / 3)-2x TiO3、Li 1+y Al y Ti 2-y (PO4)3 and Li 16-2z N z(TO4)4; wherein M represents a vacancy, N includes one or more of Zn, Cu, V and Ti, T includes Ge and / or P, 0.05≤x≤0.15, 0≤y≤0.5, 1≤z≤7; and / or, the lithium-carbon mixture includes a lithium-containing substance, and the lithium-containing substance includes one or more of LiCl, Li2C2O4, LiNO3, Li2CO3, CH3COOLi, LiOH·H2O, LiF, LiPF6, LiFSI, LiBF4, LiBOB and LiTFSI. The above-mentioned types of pore formers, electrolytes and lithium-containing substances can cooperate more fully, which is more conducive to improving the charge and discharge performance of negative electrode materials and reducing the volume expansion of negative electrode materials. In addition, the raw material sources are more extensive and the cost is lower.

[0036] In a preferred embodiment, the volume expansion rate of the modified negative electrode material is 5-15%; and / or, the specific capacity of the modified negative electrode material is 500-2000 mAh / g; and / or, the conductivity of the modified negative electrode material is 6-12 S / cm.

[0037] In another typical embodiment of the present invention, a preparation method of the above-mentioned modified negative electrode material is also provided, and the raw materials of the modified negative electrode material include graphite, a silicon source, a pore-forming agent, an electrolyte, a carbon source, a lithium source and a dispersant; the dispersant is divided into two parts, namely a first dispersant and a second dispersant; step S1, firstly the first dispersant, the silicon source, the electrolyte, the graphite and the pore-forming agent are mixed for the first time to obtain a first slurry; the D50 particle size of the silicon source in the first slurry is less than 1000nm; step S2, the first slurry is spray-dried for the first time to obtain a first solid; step S3, the first solid and the carbon source, the lithium source and the second dispersant are mixed for the second time to obtain a second slurry; step S4, the second slurry is spray-dried for the second time and calcined in a non-reactive atmosphere in sequence to obtain a modified negative electrode material.

[0038] In the preparation method of the present application, a silicon source, an electrolyte, graphite and a pore-forming agent are first mixed and spray-dried, so that the silicon source, the electrolyte and the pore-forming agent self-form an aggregate structure and are wrapped around the surface of the graphite matrix. The obtained first solid is then mixed with a carbon source and a lithium source and spray-dried, so that the carbon source and the lithium source are attached to the surface of the first solid and mixed between the silicon source, the electrolyte and the pore-forming agent. Finally, calcination is carried out under a non-reactive atmosphere, the carbon source is converted into carbon, and the lithium source is uniformly dispersed in the carbon, so as to obtain a silicon-based modified negative electrode material coated with a lithium-carbon mixture and modified with a lithium-containing electrolyte.

[0039] It should be noted that the present application specifically mixes and sprays the silicon source, electrolyte, graphite and pore-forming agent first, and then adds the carbon source and lithium source. Such operation can promote the close contact between the solid electrolyte and silicon, thereby promoting the migration of lithium ions into the silicon material and improving the surface stability of the silicon material. If the silicon source, electrolyte, graphite, pore-forming agent, carbon source and lithium source are mixed at one time, the solid electrolyte will not be in close contact with silicon, affecting the capacity of silicon.

[0040] In a preferred embodiment, the graphite includes one or more of natural graphite, flake graphite, artificial graphite and mesophase carbon microspheres; and / or, the silicon source includes one or more of silicon powder, ferrosilicon alloy, silicon-magnesium alloy, silicon-calcium alloy and silicon-manganese alloy; preferably, the D50 particle size of the silicon source is 1 to 10 μm; and / or, the carbon source includes polyethylene, polypropylene, polystyrene, phenolic resin, urea-formaldehyde resin, melamine formaldehyde resin, epoxy resin, asphalt, unsaturated polyester resin, polyurethane, citric acid, malic acid, glucose, sorbic acid, sucrose, polyacrylic acid, polyvinyl pyrrolidone, ascorbic acid, asphalt, tartaric acid and One or more of carboxymethyl cellulose; and / or, the lithium source includes one or more of LiCl, Li2C2O4, LiNO3, Li2CO3, CH3COOLi, LiOH·H2O, LiF, LiPF6, LiFSI, LiBF4, LiBOB and LiTFSI; and / or, the first dispersant and the second dispersant are independently selected from ethanol, acetone, N-methylpyrrolidone, N,N-dimethylformamide, isopropanol, ethyl acetate, propylene carbonate, butyrolactone, dimethyl sulfoxide, water, toluene, xylene, tetrahydrofuran and acetonitrile. Under the above conditions, the compatibility between the raw materials is better, which is more conducive to the preparation of the modified negative electrode material of the specific structure of the present application, and the prepared modified negative electrode material has better electrochemical performance.

[0041] In order to make the silicon particle size smaller and to make the distribution of the silicon source, electrolyte and dispersant on the graphite surface more uniform, in a preferred embodiment, in step S1, the first dispersant is divided into two parts, namely a first sub-dispersant and a second sub-dispersant, and the first mixing includes the following steps: step S11, stirring and ball-milling the first sub-dispersant, the silicon source and the electrolyte to obtain a first sub-slurry; step S12, adding the second sub-dispersant, graphite and a pore-forming agent to the first sub-slurry, performing a first grinding to obtain a first slurry; preferably, the stirring speed is 10 to 60 Hz, and the time is 1 to 10 h; and / or, the ball milling speed is 800 to 2500 r / min, and the time is 8 to 48 h; and / or, the first grinding speed is 2000 to 5000 r / min, and the time is 1 to 8 h; and / or, in terms of weight percentage, the solid content in the first slurry is 8 to 25%.

[0042] In order to make the carbon source and the lithium source more fully distributed on the surface of the first solid, in a preferred embodiment, in step S3, the second mixing is a second grinding, the rotation speed is 2000-5000 r / min, the time is 1-8 h; and / or, the solid content in the second slurry is 7-20% by weight.

[0043] In a preferred embodiment, the inlet temperature of the first spray drying and the second spray drying is 200-800° C., and the outlet temperature is 80-200° C. Under the above conditions, the particle size of the modified negative electrode material is more suitable, the particle morphology is more regular, and the packing density is higher, which is more conducive to improving the electrochemical performance of the modified negative electrode material.

[0044] In a preferred embodiment, in step S4, the calcination temperature is 500-1000°C, the time is 2-10 hours, and the non-reactive atmosphere includes inert gas and / or nitrogen, and the inert gas includes argon and / or neon. Under the above conditions, the carbon source can be more fully carbonized, and the grain size of the modified negative electrode material is more suitable and the stability is higher.

[0045] In order to make the particle size distribution of the modified negative electrode material more uniform, and to be more conducive to improving product purity, improving material morphology, and to further improve the electrochemical performance, safety and reliability of the modified negative electrode material, in a preferred embodiment, step S4 also includes the step of screening the modified negative electrode material; preferably, a sieve of 100 to 500 mesh is used for screening.

[0046] In another typical embodiment of the present invention, a modified negative electrode is provided, comprising the modified negative electrode material. The modified negative electrode of the present application is not prone to structural pulverization, has excellent conductivity, stability and cycle performance, and can fully exert its specific capacity.

[0047] In another typical embodiment of the present invention, a battery is also provided, including a negative electrode, a positive electrode and an electrolyte, wherein the negative electrode is the modified negative electrode mentioned above. The battery of the present application is not prone to structural pulverization, has excellent conductivity, stability and cycle performance, and the specific capacity can be fully utilized. Since the modified negative electrode material of the present application contains an electrolyte, it can be applied to solid-state, liquid, and semi-solid-state batteries, which is conducive to expanding the application scenarios of silicon-based materials. In a preferred embodiment, the electrolyte includes one or more of a solid electrolyte, a liquid electrolyte, and a semi-solid electrolyte.

[0048] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0049] Example 1

[0050] The schematic diagram of the preparation process of modified negative electrode materials is shown in Figure 1 .

[0051] The raw materials for the modified negative electrode material include 500g of graphite (artificial graphite with a D50 particle size of 10μm), 500g of a silicon source (silicon powder with a D50 of 4μm), 50g of a pore former (CNT nanowires with a diameter of 10nm and a length greater than 500nm), 100g of an electrolyte (solid electrolyte LiAlO2 (LAO) with a D50 of 6μm), 433g of a carbon source (PVP), 45g of a lithium source (LiBF4) and dispersants (DMF and NMP).

[0052] Step S1, add silicon source, electrolyte and 1500g dispersant DMF into a stirring tank for pre-dispersion, stirring rate 30Hz, time 1h, after discharging, add DMF 1000g cleaning equipment, and the cleaning liquid is incorporated into the slurry. Then transfer the slurry to a ball mill transfer tank, add 2000g DMF to dilute the slurry, and ball mill at a ball mill speed of 2000r / min for 24h to obtain a mixed slurry of nano silicon-LAO with a D50 particle size of 90nm. Transfer the obtained slurry to a grinding and dispersion transfer tank, add 2000g NMP to dilute the slurry, as well as graphite and pore-forming agent to obtain a slurry with a solid content of about 15%, and then grind at a grinding speed of 3500r / min for 5h.

[0053] Step S2, transferring the obtained slurry to a spray drying feeding tank for spray drying, with the inlet and outlet temperatures being 350° C. and 100° C. respectively, to obtain 864 g of spray powder.

[0054] Step S3, mixing the spray powder with 8478g NMP solution dissolved with carbon source and lithium source, and transferring the mixed solution to a grinding and dispersion transfer tank for secondary dispersion, with a grinding speed of 3000r / min and a time of 4h.

[0055] Step S4, the obtained slurry is transferred to a spray drying feeding tank for secondary spraying, and the inlet and outlet temperatures are 450°C and 120°C, respectively, to obtain 974g of powder. Afterwards, the powder is calcined at a temperature of 450°C for 4 hours in a nitrogen atmosphere. During the calcination process, the carbon source PVP is carbonized, and the lithium source is coated in the carbon layer to obtain 695g of a silicon-carbon composite material coated with a lithium salt carbon coating layer and modified with a solid electrolyte. Finally, 647g of modified negative electrode material is obtained by sieving through a 350-mesh sieve.

[0056] The structural diagram of the modified negative electrode material is shown in Figure 2The inner layer is graphite 1, and the outer layer is loaded on the surface of the inner layer. The outer layer includes an aggregated combination formed by self-stacked nano-silicon 2, electrolyte 3, and pore-forming agent 4, a lithium-carbon mixture 5 filled in the gaps of the aggregated structure, and a surface coating layer 6 formed by the lithium-carbon mixture extending to the surface of the outer layer. The SEM morphology of the modified negative electrode material is shown in Figure 3 , cross-sectional view Figure 4 , EDS diagram see Figure 5 ,in, Figure 5 Figure A in the figure shows the original EDS graph. Figure 5 Figure B shows the distribution of carbon. Figure 5 Figure C shows the distribution of oxygen. Figure 5 Figure D shows the distribution of fluorine. Figure 5 Figure E shows the distribution of aluminum. Figure 5 Figure F in the figure shows the distribution of silicon. It can be seen that the surface of the micron-scale graphite matrix is ​​loaded with an aggregate structure formed by self-assembly of nano-silicon, pore-forming agent CNT and solid electrolyte LAO, and the aggregate structure is filled with a filling layer of carbon and lithium-containing substance LiBF4, and includes a surface coating layer.

[0057] In the modified negative electrode material, the weight ratio of silicon, solid electrolyte, pore former, carbon, lithium and graphite is 50:5:10:15:6:50.

[0058] The modified negative electrode material was subjected to a half-cell test. The method for making the half-cell is as follows: the modified negative electrode material, conductive agent SP, sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 90:5:2.5:2.5 were stirred, coated and dried, and then the electrode sheet was rolled to control the compaction density to 1.2 g / cm 3 , and then assembled with lithium sheets into a 2035 model button battery.

[0059] Example 2

[0060] The only difference from Example 1 is:

[0061] The raw materials for the modified negative electrode material include 370g of graphite (artificial graphite with a D50 particle size of 6μm), 600g of a silicon source (silicon powder with a D50 of 3μm), 46g of a pore former (CNT nanowires with a diameter of 10nm and a length greater than 500nm), 74g of an electrolyte (solid electrolyte LiF with a D50 of 13μm), 409g of a carbon source (citric acid), 95g of a lithium source (Li2C2O4) and a dispersant (ethanol and water).

[0062] Step S1, add silicon source, electrolyte and 1500g dispersant ethanol into a stirring tank for pre-dispersion, stirring rate 40Hz, stirring time 2h, after discharging, add 1000g ethanol to clean the equipment, and the cleaning liquid is incorporated into the slurry. Then transfer the slurry to a ball mill transfer tank, add 2000g ethanol to dilute the slurry, ball mill, ball mill speed 2200r / min, ball mill 30h, obtain D50 particle size of 76nm nano silicon-LiF mixed slurry. The obtained slurry is transferred to a grinding and dispersion transfer tank, 1500g ethanol is added to dilute the slurry, graphite and pore-forming agent are added to obtain a slurry with a solid content of about 15%, and then grind, the grinding speed is 4000r / min, and the time is 5h.

[0063] Step S2, transferring the obtained slurry to a spray drying feeding tank for spray drying, with the inlet and outlet temperatures being 260° C. and 90° C. respectively, to obtain 821 g of spray powder.

[0064] Step S3, mixing the spray powder with 8504 g of an aqueous solution containing a carbon source and a lithium source, and transferring the mixed solution to a grinding and dispersion transfer tank for secondary dispersion, with a grinding speed of 2000 r / min and a grinding time of 3 h.

[0065] Step S4, transfer the obtained slurry to a spray drying feeding tank, perform secondary spraying, and the inlet and outlet temperatures are 300°C and 95°C, respectively, to obtain 1124g of powder. Afterwards, the powder is calcined at a temperature of 500°C and a calcination time of 4h in a nitrogen atmosphere. During the calcination process, the carbon source citric acid is carbonized, and the lithium source Li2C2O4 is converted into Li2O. At the same time, the lithium source is coated in a carbon layer to obtain 701g of a silicon-carbon composite material coated with a lithium salt carbon surface coating layer and modified with a solid electrolyte. Finally, pass through a 400-mesh sieve to obtain 686g of a modified negative electrode material.

[0066] In the modified negative electrode material, the weight ratio of silicon, solid electrolyte, pore former, carbon, lithium and graphite is 65:8:5:10:4:40.

[0067] Example 3

[0068] The only difference from Example 1 is:

[0069] The raw materials for the modified negative electrode material include 1200g graphite (natural graphite with a D50 particle size of 18μm), 150g silicon source (silicon powder with a D50 of 6μm), 45g pore former (graphene), 30g electrolyte (solid electrolyte lithium zirconate with a D50 of 3μm), 83g carbon source (polypropylene), 13g lithium source (LiFSI) and dispersant (acetonitrile and ethyl acetate).

[0070] Step S1, add silicon source, electrolyte and 1000g dispersant acetonitrile into a stirring tank for pre-dispersion, stirring rate 20Hz, stirring time 5h, discharging, adding 1000g acetonitrile to clean the equipment, and the cleaning liquid is incorporated into the slurry. Then transfer the slurry to a ball mill transfer tank, add 1000g acetonitrile to dilute the slurry, ball mill, ball milling, ball milling speed 1500r / min, ball milling 32h, obtain D50 particle size of 94nm nano-silicon-lithium zirconate mixed slurry. The obtained slurry is transferred to a grinding and dispersion transfer tank, 5000g ethanol is added to dilute the slurry, graphite and pore-forming agent are added to obtain a slurry with a solid content of about 15%, and then ground, the grinding speed is 4500r / min, and the time is 5h.

[0071] In step S2, the obtained slurry is transferred to a spray drying feeding tank for spray drying. The inlet and outlet temperatures are 400° C. and 120° C. respectively, and 1214 g of powder is obtained.

[0072] Step S3, obtain the spray powder, mix it with 7096g of ethyl acetate solution dissolved with carbon source and lithium source, and transfer the mixed solution to the grinding and dispersion transfer tank for secondary dispersion, the grinding speed is 2500r / min, and the time is 4h.

[0073] Step S4, the obtained slurry is transferred to a spray drying feeding tank for secondary spraying, and the inlet and outlet temperatures are 280°C and 85°C, respectively, to obtain 1102g of powder. Afterwards, the powder is calcined at a temperature of 550°C for 3h in a nitrogen atmosphere. During the calcination process, the carbon source polypropylene is carbonized, and the lithium source is coated in the carbon layer to obtain 857g of a silicon-carbon composite material coated with a lithium salt carbon surface coating layer and modified with a solid electrolyte. Finally, 815g of modified negative electrode material is obtained by passing through a 300-mesh sieve.

[0074] In the modified negative electrode material, the weight ratio of silicon, solid electrolyte, pore former, carbon, lithium and graphite is 10:2:3:3:1:80.

[0075] Example 4

[0076] The only difference from Example 1 is that the types and contents of raw materials are different.

[0077] Specifically, the raw materials of the modified negative electrode material include graphite (natural graphite with a particle size of 30 μm at D50), silicon source (silicon powder with a particle size of 1 μm at D50), pore-forming agent (silver nanowire with a diameter of 60 nm and a length greater than 1 μm), electrolyte (solid electrolyte Li with a particle size of 6 μm at D50), and 1.5 Al 0.5 Ti 1.5 (PO4)3), carbon source (asphalt), lithium source (LiBOB) and dispersant (butyrolactone and tetrahydrofuran).

[0078] Calculated by weight percentage, among the raw materials, graphite accounts for 79.2%, silicon source accounts for 9.9%, pore former accounts for 2%, electrolyte accounts for 2%, carbon source accounts for 5.9%, lithium source accounts for 1%, and dispersant accounts for 83%.

[0079] In the modified negative electrode material, the weight ratio of silicon, solid electrolyte, pore former, carbon, lithium and graphite is 10:2:2:3:1:80.

[0080] Example 5

[0081] The only difference from Example 1 is that the types and contents of raw materials are different.

[0082] Specifically: the raw materials of the modified negative electrode material include graphite (mesophase carbon microsphere graphite with a D50 particle size of 5μm), silicon source (silicon powder with a D50 of 1μm), pore-forming agent (copper nanowire, diameter 50nm, length greater than 600nm), electrolyte (solid electrolyte Li8Cu4(PO4)4 with a D50 of 6μm), carbon source (phenolic resin), lithium source (LiF) and dispersant (acetonitrile and acetone).

[0083] Calculated by weight percentage, among the raw materials, graphite accounts for 5.6%, silicon source accounts for 44.4%, pore former accounts for 5.6%, electrolyte accounts for 16.7%, carbon source accounts for 22.2%, lithium source accounts for 5.6%, and dispersant accounts for 84%.

[0084] In the modified negative electrode material, the weight ratio of silicon, solid electrolyte, pore former, carbon, lithium and graphite is 80:30:10:20:10:10.

[0085] Example 6

[0086] The only difference from Example 1 is:

[0087] Step S1: 500 g of silicon powder with a D50 of 4 μm and LLZO (Li7La3Zr2O 12 ) 100g and 1500g dispersant DMF are added to the stirring tank for pre-dispersion, the stirring rate is 10Hz, the time is 10h, after the material is discharged, 1000g DMF is added to clean the equipment, and the cleaning liquid is incorporated into the slurry. Then the slurry is transferred to the ball mill transfer tank, and 2000g DMF is added to dilute the slurry, and ball milling is performed at a ball milling speed of 800r / min for 48h to obtain a nano-silicon-LLZO mixed slurry with a D50 particle size of 104nm. The obtained slurry is transferred to the grinding and dispersion transfer tank, 2000g NMP is added to dilute the slurry, as well as 500g artificial graphite (particle size 10μm), 50g pore-forming agent BN nanowires (diameter 30nm, length greater than 500nm), to obtain a slurry with a solid content of about 15%, and then ground at a grinding speed of 2000r / min for 8h.

[0088] Step S2, transferring the obtained slurry to a spray drying feeding tank for spray drying, with the inlet and outlet temperatures being 350° C. and 100° C. respectively, to obtain 885 g of powder.

[0089] Step S3, mixing the obtained spray powder with 8500g of NMP solution dissolved with 438g of carbon source PVP and 47g of lithium source LiBF4, and transferring the mixed solution to a grinding and dispersion transfer tank for secondary dispersion, with a grinding speed of 2000r / min and a time of 8h.

[0090] Step S4, transfer the obtained slurry to a spray drying feeding tank, perform secondary spraying, and the inlet and outlet temperatures are 340°C and 106°C, respectively, to obtain 989g of powder. Afterwards, the powder is calcined at a temperature of 500°C and a calcination time of 10h in a nitrogen atmosphere. During the calcination process, the carbon source PVP is carbonized, and the lithium source is coated in the carbon layer to obtain 704g of a silicon-carbon composite material coated with a lithium salt carbon surface coating layer and modified with a solid electrolyte. Finally, sieve through a 350-mesh sieve to obtain 683g of the final modified negative electrode material.

[0091] In the modified negative electrode material, the weight ratio of silicon, solid electrolyte, pore former, carbon, lithium and graphite is 50:10:5:15:6:50.

[0092] Example 7

[0093] The only difference from Example 1 is:

[0094] Step S1: 500 g of silicon powder with a D50 of 4 μm and LLZO (Li7La3Zr2O 12 ) 100g and 1500g dispersant DMF were added to the stirring tank for pre-dispersion, with a stirring rate of 60Hz for 1h. After discharging, 1000g of DMF was added to clean the equipment, and the cleaning liquid was incorporated into the slurry. Then the slurry was transferred to the ball mill transfer tank, and 2000g of DMF was added to dilute the slurry, and ball milling was performed at a ball milling speed of 2500r / min for 8h to obtain a nano-silicon-LLZO mixed slurry with a D50 particle size of 97nm.

[0095] The obtained slurry was transferred to a grinding and dispersion transfer tank, and 2000g NMP was added to dilute the slurry, as well as 500g artificial graphite (particle size 10μm) and 50g pore-forming agent BN nanowires (diameter 30nm, length greater than 500nm) to obtain a slurry with a solid content of about 15%, and then ground at a grinding speed of 5000r / min for 1h.

[0096] Step S2, transferring the obtained slurry to a spray drying feeding tank for spray drying, with the inlet and outlet temperatures being 350° C. and 100° C. respectively, to obtain 824 g of powder.

[0097] Step S3, obtain the spray powder, mix it with 8351g of NMP solution dissolved with 425g of carbon source PVP and 43g of lithium source LiBF4, and transfer the mixed solution to the grinding and dispersion transfer tank for secondary dispersion, with a grinding speed of 5000r / min and a time of 1h.

[0098] Step S4, the obtained slurry is transferred to a spray drying feeding tank for secondary spraying, and the inlet and outlet temperatures are 800°C and 200°C, respectively, to obtain 949g of powder. Afterwards, the powder is calcined at a calcination temperature of 1000°C and a calcination time of 2h in a nitrogen atmosphere. During the calcination process, the carbon source PVP is carbonized, and the lithium source is coated in the carbon layer to obtain 671g of a silicon-carbon composite material coated with a lithium salt carbon surface coating layer and modified with a solid electrolyte. Finally, sieve through a 300-mesh sieve to obtain 622g of the final modified negative electrode material.

[0099] In the modified negative electrode material, the weight ratio of silicon, solid electrolyte, pore former, carbon, lithium and graphite is 50:10:5:15:6:50.

[0100] Comparative Example 1

[0101] The only difference from Example 1 is that no pore former is added.

[0102] In the modified negative electrode material, the weight ratio of silicon, solid electrolyte, carbon, lithium and graphite is 50:10:15:6:50.

[0103] Analysis shows that if pore-forming agents are not added, the specific capacity will be reduced and the initial efficiency will decrease. This is mainly because the composite material does not have sufficient space to reserve for the volume expansion of the silicon-based material during charging and discharging, which limits the capacity and deteriorates the surface stability of the material.

[0104] Comparative Example 2

[0105] The only difference from Example 2 is that no solid electrolyte is added.

[0106] In the modified negative electrode material, the weight ratio of silicon, pore former, carbon, lithium and graphite is 65:5:10:4:40.

[0107] Analysis shows that not adding solid electrolytes will also lead to a decrease in capacity and initial efficiency. This is mainly because without solid electrolytes, the multi-layer diffusion of lithium ions in the material is limited, making it impossible to fully utilize the capacity.

[0108] Comparative Example 3

[0109] The only difference from Example 3 is that no lithium source is added.

[0110] In the modified negative electrode material, the weight ratio of silicon, solid electrolyte, pore former, carbon and graphite is 10:2:3:3:80.

[0111] Analysis shows that the absence of lithium salt in the carbon layer will lead to a decrease in capacity utilization and initial efficiency. This is mainly because the carbon layer without lithium salt has an increased number of reactions between the material surface and the electrolyte, resulting in an increase in the consumption of active lithium.

[0112] The particle size, electrochemical performance, cycle performance, and conductive performance test results of the silicon particles of the modified negative electrode materials prepared in the above examples and comparative examples are shown in Table 1.

[0113] Test method:

[0114] Specific capacity, initial efficiency and cycle performance tests: The tests were conducted at 0.2C, 25°C, and a charge and discharge voltage range of 0.005 to 2V; the capacity retention rate was examined after 100 cycles.

[0115] Volume expansion rate: After the first charge and discharge, disassemble the battery, clean the electrode with dimethyl carbonate, and dry it at 45℃. Then, test the electrode thickness and compare it with that before charge and discharge to examine the expansion rate of the electrode.

[0116] Conductivity: Conduct conductivity test on the electrode pieces containing silicon-based negative electrode materials used to make buckle batteries.

[0117] Table 1

[0118]

[0119] As can be seen from the above, compared with the comparative example, the embodiment of the present application can fully utilize the capacity of silicon and the first efficiency of the electrode is high by nano-sizing silicon, designing pores, introducing solid electrolytes, and coating the lithium-carbon mixture, while loading the silicon material on a micron-sized graphite matrix. Among them, the porous design can provide volume expansion of the silicon material during charging and discharging, which is beneficial to maintaining the integrity of the material and improving the stability and capacity of the material. The introduction of solid electrolytes can promote the diffusion and migration of lithium ions in the material, which is beneficial to the capacity of silicon-based materials. In addition, the silicon-based material is coated with carbon containing lithium salts, which can not only improve the conductivity of the silicon-based material, but also reduce the side reactions between the electrolyte and the carbon-coated surface and improve the surface stability of the silicon-based material. The material contains a solid electrolyte and is suitable for solid-state battery applications, expanding the application scenarios of silicon-based materials.

[0120] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the negative electrode has higher safety and better electrochemical performance.

[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified negative electrode material, characterized in that: comprising an inner layer and an outer layer covering the surface of the inner layer, The inner layer comprises graphite; The outer layer includes an aggregate structure and a lithium-carbon mixture; The aggregate structure is formed by self-accumulation of nano-silicon, pore-forming agent and electrolyte, and has gaps in the aggregate structure; The lithium-carbon mixture fills the gaps in the aggregate structure and extends to the surface of the outer layer to form a surface coating layer.

2. The modified negative electrode material according to claim 1, characterized in that In the modified negative electrode material, The thickness ratio of the inner layer to the outer layer is (0.25-16):1; preferably, the thickness of the outer layer is 200-1000 nm, wherein the thickness of the surface coating layer is 5-100 nm; and / or, The weight ratio of the nano-silicon to the graphite is (10-80):(10-80); and / or, the weight ratio of the pore former to the graphite is (1-10):(10-80); and / or, the weight ratio of the electrolyte to the graphite is (2-30): (10-80); and / or, the weight ratio of the lithium-carbon mixture to the graphite is (4-40):(10-80).

3. The modified negative electrode material according to claim 1 or 2, characterized in that: In the modified negative electrode material, The graphite has a particle size D50 of 5 to 30 μm; and / or, The particle size D50 of the nano-silicon is 10 to 150 nm; and / or, The diameter of the pore-forming agent is 5 to 200 nm.

4. The modified negative electrode material according to any one of claims 1 to 3, characterized in that: The pore former includes one or more of silver nanowires, copper nanowires, carbon nanotubes, carbon fibers, zinc oxide nanorods, silicon carbide nanowires, boron nitride nanowires and graphene; and / or, The electrolyte includes lithium aluminum oxide, lithium phosphate, lithium tantalate, lithium zirconate, LiF, lithium rubidium oxide, Li7La3Zr2O 12 , Li 3x La (2 / 3)-x M (1 / 3)-2x TiO3、Li 1+y Al y Ti 2-y (PO4)3 and Li 16-2z N z (TO4) 4; wherein M represents a vacancy, N comprises one or more of Zn, Cu, V and Ti, T comprises Ge and / or P, 0.05≤x≤0.15, 0≤y≤0.5, 1≤z≤7; and / or, The lithium-carbon mixture includes a lithium-containing substance, and the lithium-containing substance includes one or more of LiCl, Li2C2O4, LiNO3, Li2CO3, CH3COOLi, LiOH·H2O, LiF, LiPF6, LiFSI, LiBF4, LiBOB and LiTFSI.

5. The method for preparing the modified negative electrode material according to any one of claims 1 to 4, characterized in that: The raw materials of the modified negative electrode material include graphite, a silicon source, a pore former, an electrolyte, a carbon source, a lithium source and a dispersant; the dispersant is divided into two parts, namely a first dispersant and a second dispersant; The preparation method comprises the following steps: Step S1, firstly mixing the first dispersant, the silicon source, the electrolyte, the graphite and the pore former to obtain a first slurry; the silicon source in the first slurry has a particle size D50 of less than 1000 nm; Step S2, performing a first spray drying on the first slurry to obtain a first solid; Step S3, performing a second mixing of the first solid, the carbon source, the lithium source, and the second dispersant to obtain a second slurry; Step S4, subjecting the second slurry to a second spray drying and a non-reactive atmosphere calcination in sequence to obtain the modified negative electrode material.

6. The preparation method according to claim 5, characterized in that: The graphite includes one or more of natural graphite, flake graphite, artificial graphite and mesophase carbon microspheres; and / or, The silicon source comprises one or more of silicon powder, ferrosilicon alloy, silicon-magnesium alloy, silicon-calcium alloy and silicon-manganese alloy; preferably, the D50 particle size of the silicon source is 1 to 10 μm; and / or, The carbon source comprises one or more of polyethylene, polypropylene, polystyrene, phenolic resin, urea-formaldehyde resin, melamine-formaldehyde resin, epoxy resin, asphalt, unsaturated polyester resin, polyurethane, citric acid, malic acid, glucose, sorbic acid, sucrose, polyacrylic acid, polyvinyl pyrrolidone, ascorbic acid, asphalt, tartaric acid and carboxymethyl cellulose; and / or, The lithium source includes one or more of LiCl, Li2C2O4, LiNO3, Li2CO3, CH3COOLi, LiOH·H2O, LiF, LiPF6, LiFSI, LiBF4, LiBOB and LiTFSI; and / or, The first dispersant and the second dispersant are independently selected from one or more of ethanol, acetone, N-methylpyrrolidone, N,N-dimethylformamide, isopropanol, ethyl acetate, propylene carbonate, butyrolactone, dimethyl sulfoxide, water, toluene, xylene, tetrahydrofuran and acetonitrile.

7. The preparation method according to claim 5 or 6, characterized in that: In the step S1, the first dispersant is divided into two parts, namely a first sub-dispersant and a second sub-dispersant, and the first mixing includes the following steps: Step S11, stirring and ball-milling the first sub-dispersant, the silicon source, and the electrolyte to obtain a first sub-slurry; Step S12, adding the second sub-dispersant, the graphite and the pore-forming agent to the first sub-slurry, performing a first grinding to obtain the first slurry; Preferably, the stirring speed is 10 to 60 Hz and the time is 1 to 10 h; and / or, The ball mill has a rotation speed of 800 to 2500 r / min and a time of 8 to 48 hours; and / or, The first grinding has a rotation speed of 2000-5000 r / min and a time of 1-8 h; and / or, Calculated by weight percentage, the solid content of the first slurry is 8-25%.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In step S3, the second mixing is a second grinding, the rotation speed is 2000-5000 r / min, and the time is 1-8 h; and / or, Calculated by weight percentage, the solid content of the second slurry is 7-20%; and / or, Independently, the inlet temperature of the first spray drying and the second spray drying is 200-800°C, and the outlet temperature is 80-200°C; and / or, In the step S4, the calcination temperature is 500-1000° C., the time is 2-10 hours, and the non-reactive atmosphere includes an inert gas and / or nitrogen, and the inert gas includes argon and / or neon.

9. A modified negative electrode, characterized in that: The modified negative electrode material comprises the modified negative electrode material according to any one of claims 1 to 4.

10. A battery comprising a negative electrode, a positive electrode and an electrolyte, characterized in that: The negative electrode is the modified negative electrode according to claim 9.